Developing Malaysian 3D cadastre system-preliminary findings - Hassan, Muhammad Imzan; Abdul Rahman, Alias; Stoter, Jantien (2006)
2D cadastre being practice in Malaysia for decades and at the moment it provides vital land and property information like ownerships of the parcels for most parts of the country. The current 2D cadastre system is regularly updated both in rural and in urban areas by the national survey agency (NMA), i.e. the Department of Survey and Mapping (JUPEM). NMA is the responsible agency with survey and mapping to deal on the technical part of producing the cadastral map. They have a very well designed system called Cadastral Database Management System (CDMS) with Digital Cadastral Database (DCDB). On the other hands, the ownership information (who owns what) comes from Land and Mines Offices (PTG) and all these information are considered two-dimensional (2D) in nature. Typical information related to parcels and property ownerships like parcel numbers or IDs, parcel’s geometry and dimensions, etc. are digitally available. In Land Office, they have their own registration system called Computerized Land Registration System (CLRS). Unfortunately, these valuable information being handled by two different agencies in two non-integrated systems. It can be realized that these information still in 2D system and most of the existing 2D cadastre systems are hardly able to provide more realistic and meaningful information to users. With the rapid development of hardware, software and knowledge, we believed Malaysia are ready to develop a 3D Cadastre System to solve the problems with the complexity of cadastral registration of 3D property situations. In Malaysia, hybrid 3D cadastre will be discussed as this model was proposed by previous research work, i.e. Stoter (2004). However, the design system should be realistic and practical to be applied based on Malaysian cadastral environment either on regulation or historically. The aim of this paper is to discuss some initial literature reviews of the subject or problem with respect to current 2D Cadastre System and 2D registration system in Malaysia. The early findings of the problems will be served as starting point in developing and addressing a much bigger problem for a PhD research work.